The Impact of Knowledge Management on Strategic Management Practices - Alghofeli, Mashael Shaye (International Journal of Informatics and Information Systems, 2022)
Purpose: The study aims to assess the effect of knowledge management on strategic management in the General Administration of Education in Jeddah, Saudi Arabia. Design/methodology/approach: The research employed a quantitative method and descriptive analysis was conducted using SPSS21 and AMOS 23. The design, which has six independent variables and a single dependent variable. The study uses the questionnaire tool, a questionnaire was developed by the researcher, and distributed to a sample of 316 employees of the General Administration of Education in Jeddah in Saudi Arabia. and the questionnaire is two-part. The first is for primary verses such as age, experience, degree of employment, scientific qualification, and average income, and the second part is to address the knowledge management dimensions (knowledge distribution, knowledge acquisition, knowledge diagnosis, knowledge storage, knowledge generation, knowledge application) and its relationship to strategic management practices, the testing measurement validity and reliability could be occurred by EFA then analyzed the data by using multi regression .The study is based on the descriptive analytical approach to suit its purposes, free from reviewing and reviewing the theoretical literature on knowledge management and strategic management practices, in addition to reviewing previous relevant studies. Findings: knowledge management processes impact on Strategic Management Practices when testing the relationship between knowledge management processes and strategic management practices by structural equation modeling SEM, but the knowledge acquisition has no significant effect on strategic management practices.Research limitations/implications: The research was applied to the General Administration of Education in Jeddah, in Saudi Arabia, and the research was limited to the city of Jeddah only, and these tools can also be applied to other government institutions, especially in departments that work in providing services to the public. It is believed that knowledge management will have a role Effective if it is applied in service institutions that seek to apply strategic management to meet the increasing needs of the public.Originality/value: The paper is of theoretical and practical importance, as the theoretical importance is the literary addition to which research contributes to the theoretical enrichment of scientific literature on knowledge management and strategic management practices, The paper also has its applied importance as it deals with the effect of knowledge management on implementing strategic management practices. This will be applied in Jeddah, Saudi Arabia, which contributes to developing strategic performance based on knowledge management.